SONIPAT IN ANCIENT TIMES: A HISTORICAL STUDY - Vashisht, Naveen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper highlights the ancient history of Sonipat, a major historical city located in the Indian state of Haryana. Historically identified by the name "Swarnaprastha", Sonipat was a major urban centre in the Vedic and Mahajanapada eras. This research paper examines its geographical importance due to its strategic location on major trade routes linking the Indus Valley with the Ganges Basin, which facilitated its development as a commercial and cultural centre. This research integrates archaeological findings such as ancient fortifications, inscriptions and artefacts with literary sources including Vedic texts, the Mahabharata, and histories of the Mauryan and Gupta periods. These sources collectively shed light on the role of Sonipat in regional politics, economy and culture. This study discusses Sonipat's connection with the Kuru dynasty and its significance in the context of the Mahabharata, exploring interpretations of its historical and mythological roles. Additionally, it analyses the city's growth and administrative roles during the Mauryan and Gupta empires, highlighting its contribution to regional governance and trade. This research highlights Sonipat's historical significance and its contribution to the cultural and economic landscape of ancient India and, by synthesizing archaeological and textual evidence, provides a comprehensive overview of Sonipat's development and its influence on the broader historical narrative of the region.